The kind leader : a practical guide to eliminating fear, creating trust, and leading with kindness - Ross, Karyn (Tantor Media, Inc., 2022)
Kindness and leadership aren't often synonymous. Ask someone to describe "good leadership" to you and you will hear many adjectives used. And though there are many more that come to mind, kindness isn't one of them. And here's the problem with that. What a leader models-how they think, speak, and act-influences the people they lead. Leaders who think, speak, and act unkindly give legitimacy and permission to those they lead to think, speak, and act in exactly the same unkind ways. In an increasingly fragmented, polarized, and divided world, we need leaders who will bring people together, not divide them. We need kindness to become synonymous with good leadership. The purpose of this book is to teach leaders how to lead with kindness so they can influence the people they lead to create kinder workplaces, organizations, and the world. This book gives you a deep theoretical understanding of the importance of leading with kindness and also provides practical exercises for you to use. By the time you finish the book, you will feel confident in your ability to lead with kindness and also to address organizational problems at work, at home, and in the community with kindness